2021
DOI: 10.3892/mmr.2021.12084
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan 2, 3‑dioxygenase promotes proliferation, migration and invasion of ovarian cancer cells

Abstract: Tryptophan 2,3-dioxygenase (TDO2) is a key rate-limiting enzyme in the kynurenine pathway and promotes tumor growth and escape from immune surveillance in different types of cancer. The present study aimed to investigate whether TDO2 serves a role in the development of ovarian cancer. Reverse transcription-quantitative PCR and western blotting were used to detect the expression of TDO2 in different cell lines. The effects of TDO2 overexpression, TDO2 knockdown and TDO2 inhibitor on ovarian cancer cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
1
11
1
Order By: Relevance
“…In the present study, we identified that TDO2 is highly expressed in 20 types of cancer, including BLCA, BRCA, CESC, COAD, ESCA, GBM, HNSC, KIRC, LUAD, LUSC, OV, PAAD, PRAD, READ, SKCM, STAD, TGCT, THCA, UCEC, and UCS, which are in line with previous findings [8][9][10][24][25][26][27][28]. However, Wu et al found that TDO2 was overexpressed in HCC, and their overexpression was correlated with tumor progression and poor prognosis [29,30], which contradicts our current results.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we identified that TDO2 is highly expressed in 20 types of cancer, including BLCA, BRCA, CESC, COAD, ESCA, GBM, HNSC, KIRC, LUAD, LUSC, OV, PAAD, PRAD, READ, SKCM, STAD, TGCT, THCA, UCEC, and UCS, which are in line with previous findings [8][9][10][24][25][26][27][28]. However, Wu et al found that TDO2 was overexpressed in HCC, and their overexpression was correlated with tumor progression and poor prognosis [29,30], which contradicts our current results.…”
Section: Discussionsupporting
confidence: 93%
“…The IDO1 expression pattern in our OCCC cohort was different from that in ovarian serous carcinoma, previously reported to range from 59% to 71%. 32,41 Efforts should be made to validate our findings.…”
Section: T a B L E 3 Relations Between Expression Of Trp Catabolising...mentioning
confidence: 81%
“…In line with this, high IDO expression in ovarian cancer cells was found to be correlated with lower levels of tumour‐infiltrating lymphocytes, advanced surgical stage and decreased survival 13 . Similarly, TDO2 catabolises the degradation of Trp to Kyn and is upregulated in ovarian cancer tissues compared with normal ovarian tissues, promoting the proliferation, migration and invasion of ovarian cancer cells 32 . Recently, overexpression of IL4I1 was shown to activate AHR and promote tumour progression 22 .…”
Section: Introductionmentioning
confidence: 77%
“…It is reported that TDO2 is highly expressed in many tumors and promotes tumor progression, and as a promising cancer treatment target, it has attracted more and more attention. Reports revealed that inhibition of TDO2 can repress the proliferation, migration and invasion of ovarian cancer and colorectal cancer ( 44 , 45 ). The prognostic signature was probably associated with TDO2 expression and TDO2 checkpoint pathway in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%